2010
DOI: 10.1111/j.1601-6343.2009.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Skull thickness in patients with clefts

Abstract: CL women had a significantly thinner occipital bone compared with CL men (p = 0.027). Women with UCLP had significantly thicker occipital bone than the control women (incomplete CL) (p = 0.014). The study showed gender differences in skull thickness in different cleft types. It also demonstrated that particularly the occipital bone deviated in patients with UCLP, which may explain the considerable deviations in jaw shape and position, previously registered in patients with UCLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A recent study showed that also skull thickness differs in different cleft groups, particularly the occipital bone, which differed in complete cleft lip and palate from the thickness registered in cleft lip [10].…”
Section: Introductionmentioning
confidence: 98%
“…A recent study showed that also skull thickness differs in different cleft groups, particularly the occipital bone, which differed in complete cleft lip and palate from the thickness registered in cleft lip [10].…”
Section: Introductionmentioning
confidence: 98%
“…The study showed gender differences in skull thickness in different cleft types. Furthermore, it was demonstrated that particularly the occipital bone was thicker in patients with combined cleft lip and palate [105].…”
Section: B Postnatalmentioning
confidence: 99%
“…The first report on calvarial thickness was by Anderson (2) in 1882, which was followed by Todd (3) in 1924. Then further studies were estimated and analyzed for long period and becoming a critical issue for medical, forensic medicine, and anthropological studies, and different relationships between calvarial thickness, gender, age, general body build mass, and race have been studied pattern of cranial vault thickness in normal and pathological development have been discussed over years (15)(16)(17)(18)(19) . The relationship between calvarial thickness and skeletal malocclusion has not been published until very recently (20,21) .…”
Section: Introductionmentioning
confidence: 99%